2022
DOI: 10.29303/jppipa.v8i6.2179
|View full text |Cite
|
Sign up to set email alerts
|

Development of STEM Learning based Android to Improving Students’ Logical Thinking Skills

Abstract: This study aims to determine the feasibility of STEM learning based Android that was developed to increase students' logical thinking skills competence, as well as to determine student readiness with the renewal of learning modes and student responses to the developed learning media. This study uses the type of Research and Development (R&D) research with adapted from Borg & Gall (2007) dan 4-D model procedural. The learning media product being developed in the form of an android application with a STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Subsequently, the AR textbook was created to enable students to engage with the material firsthand through object observation and written communication of their understanding. As a result, the knowledge that students acquire from interacting with this textbook through Augmented Reality becomes the technology a possible teaching tool (Setiawaty et al, 2022;Yaniawati et al, 2023) Furthermore, the results of the analysis of the prerequisites for the mastery of concepts test are as follows. Based on Table 7 and 8, the pretest and posttest scores have a variance that is not the same level (inhomogeneous), and the control class scores are not normally distributed, and the experimental class scores are normally distributed.…”
Section: N-gain Homogeneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the AR textbook was created to enable students to engage with the material firsthand through object observation and written communication of their understanding. As a result, the knowledge that students acquire from interacting with this textbook through Augmented Reality becomes the technology a possible teaching tool (Setiawaty et al, 2022;Yaniawati et al, 2023) Furthermore, the results of the analysis of the prerequisites for the mastery of concepts test are as follows. Based on Table 7 and 8, the pretest and posttest scores have a variance that is not the same level (inhomogeneous), and the control class scores are not normally distributed, and the experimental class scores are normally distributed.…”
Section: N-gain Homogeneousmentioning
confidence: 99%
“…Therefore, teachers must adapt aspects of pedagogy and technology in the teaching and learning process. However, to make learning successful, there needs to be technology, such as creating active and contextual learning activities, so teachers need to have digital literacy skills when using digital devices (Kaimara et al, 2021;Daniela, 2021;Setiawaty et al, 2022). The application of AR provides a new perspective on learning activities, or science experiments carried out in laboratories, which has an essential place in science education (Yilmaz, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities to improve physics learning outcomes by utilizing android-based learning media, such as research conducted (Susanto et al, 2022), show that androidbased learning media can improve student learning outcomes. In addition, using android-based learning media can improve student learning outcomes and enhance students' logical thinking skills (Setiawaty et al, 2022).…”
Section: Figure 2 Teacher Activity In the Experiments Classmentioning
confidence: 99%
“…This makes Android attractive and has recently been used as a learning medium because users can create Android-based applications. Several previous studies have shown that Android-based learning media can be used in learning (Iqbal et al, 2016;Rasmawan et al, 2021;Zulherman et al, 2021;Setiawan et al, 2023;Setiawaty et al, 2022). Android as a learning medium has been widely developed and gives positive results in the learning process, including in learning physics (Astuti et al, 2017;Payu et al, 2023;Febyanti et al, 2022;Ntobuo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%